Evaluation of public policies in the Northeast: what are we looking for? - Arcoverde, Ana Cristina Brito (Revista Aval, 2021)
Our purpose in the present text is to work, through the analysis of secondary data, the evaluation in its brief historicity,presenting then the place it occupies in the structure of the nine States that form the Brazilian Northeast, and to try to answer thequestion: what are we looking for? We understand the evaluation of public policies as a critical analysis, as a process and procedureinherent to the planning process of public action that qualifies State intervention, when it comes to an emancipatory corporate project,and that responds to social demands as an expression of public interests. The evaluation is historic, legitimized in 2004, occupies aprominent place in the Planning Secretariats of the northeastern states, but still within the framework of the hegemonic managerialperspective. The challenge of evaluating public policies is to seek results that transform the situation unchanged. Qualifying theevaluation and developing skills is the responsibility of the public manager, committed to the public thing.